A Novel Role for C5a in B-1 Cell Homeostasis - Bröker, Katharina; Figge, Julia; Magnusen, Albert F.; Manz, Rudolf A.; Köhl, Jörg; Karsten, Christian M. (Frontiers in Immunology, 2018)
B-1 cells constitute a unique subpopulation of lymphocytes residing mainly in body cavities like the peritoneal cavity (PerC), but are also found in spleen and bone marrow. As innate-like B cells, they mediate first line immune defense through low affinity natural IgM (nIgM) antibodies. PerC B-1 cells can egress to the spleen and differentiate into nIgM antibody-secreting plasma cells that recognize conserved exogenous and endogenous cellular structures. Homing to and homeostasis within the peritoneal cavity are regulated by the chemokine CXCL13 released by PerC macrophages and stroma cells. However, the exact mechanisms underlying the regulation of CXCL13 and B-1 homeostasis are not fully explored. B-1 cells play important roles in the inflammatory response to infection, autoimmunity, ischemia/reperfusion injury, obesity and atherosclerosis. Remarkably, this list of inflammatory entities has a strong overlap with diseases that are regulated by complement suggesting a link between B-1 cells and the complement system. Interestingly, up to now, no data exist regarding the role of complement in B-1 cell biology. Here, we demonstrate for the first time that C5a regulates B-1 cell steady state dynamics within the peritoneum, the spleen and the bone marrow. We found decreased B-1a cell numbers in the peritoneum and the spleen of C5aR1-/- mice associated with increased B1-a and B1-b numbers in the spleen and high serum titers of nIgM antibodies directed against phosphorylcholine and several pneumococcal polysaccharides. Similarly, peritoneal B-1a cells were decreased in the peritoneum and splenic B-1a and B-1b cells were increased in C5aR2-/- mice. The decrease in peritoneal B-1 cell numbers was associated with decreased peritoneal CXCL13 levels in C5aR1-/- and C5aR2-/- mice. In search for mechanisms, we found that combined TLR2 and IL-10 receptor activation in PerC macrophages induced strong CXCL13 production, which was significantly reduced in cells from C5aR1- and C5aR2-deficient mice and after combined C5aR-targeting. Such stimulation also induced marked local C5 production by PerC macrophages and C5a generation. Importantly, peritoneal in vivo administration of C5a increased CXCL13 production. Taken together, our findings suggest that local non-canonical C5 activation in PerC macrophages fuels CXCL13 production as a novel mechanism to control B-1 cell homeostasis.